DEIKSIS DALAM NOVEL SABTU BERSAMA BAPAK KARYA ADHITYA MULYA (KAJIAN PRAGMATIK) - Mustopa, Ali; Rahmawati, Dewi; Lindayani, Lilik Rita (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
This study aims to explain how the 3 types of deixis are used in the novel “Sabtu bersama Bapak” by Adhitya Mulya. This study used a qualitative descriptive method in which the data in the study were obtained from the novel “Sabtu bersama Bapak”. The data in this study are in the form of sentences obtained from dialogues in the novel “Sabtu bersama Bapak”, in which there are 3 types of deixis, namely persona deixis, place deixis, and time deixis. The data collection process in this study uses reading and note-taking techniques. The process of analyzing the data in this study includes 3 procedures, namely data reduction, data presentation, and data verification. The results of the study found that there were 3 types of deixis used by the author in the novel “Sabtu Bersama Bapak”, namely persona deixis, place deixis, and time deixis with a total usage of 23 data.